Arrhenius parameters of the bacteriorhodopsin photocycle in dried oriented samples. - Váró, G (1985)
In dried oriented samples of purple membranes isolated from Halobacterium halobium the Arrhenius parameters of the photocycle showed an abrupt change at a water content of approximately 80 H2O molecules per bacteriorhodopsin molecule. This makes probable the existence of a water-dependent conformational change of the protein. This result underlines the importance of water in the proton-conduction mechanism inside the protein. The effect of the external electric potential on the rate constants of the photoelectric signals was also measured. The data demonstrate that the membrane potential affects the steps of the proton transport during the photocycle.